2020
DOI: 10.12681/mms.21201
|View full text |Cite
|
Sign up to set email alerts
|

Bryozoan diversity of Cyprus (eastern Mediterranean Sea): first results from census surveys (2011–2018)

Abstract: The Mediterranean bryozoan fauna is considered to be well studied compared to other marine areas of the world. However, in the Levantine Basin, bryozoan diversity has not yet been adequately documented. This report presents the first systematic and most comprehensive study of bryozoans sampled in Cyprus during census surveys from 2011 to 2018. The specimens were collected between 9 and ~620 m depth from several habitat types (mainly soft-bottom environments but also hard natural/artificial substrata, ancient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
(47 reference statements)
0
4
1
Order By: Relevance
“…However, part of the reported lower diversity in the Eastern Mediterranean may be attributed to insufficient sampling: every time a taxonomic group is thoroughly studied, a remarkable number of previously unreported native species is recorded (e.g. Morri et al 2009;Idan et al 2018;Crocetta et al 2020;Achilleos et al 2020;Castelló et al 2020). Our results are no exception: the 43 newly reported species constitute an increase of 7% in relation to the 624 native molluscs previously recorded from Israel.…”
Section: Is Biodiversity Underestimation a Broader Pattern In The Eascontrasting
confidence: 62%
“…However, part of the reported lower diversity in the Eastern Mediterranean may be attributed to insufficient sampling: every time a taxonomic group is thoroughly studied, a remarkable number of previously unreported native species is recorded (e.g. Morri et al 2009;Idan et al 2018;Crocetta et al 2020;Achilleos et al 2020;Castelló et al 2020). Our results are no exception: the 43 newly reported species constitute an increase of 7% in relation to the 624 native molluscs previously recorded from Israel.…”
Section: Is Biodiversity Underestimation a Broader Pattern In The Eascontrasting
confidence: 62%
“…We can confidently rule out the overlooking of M. hastingsae by Harmelin et al (2016) because he coauthored the description of the species (Harmelin et al, 2011). Furthermore, from the examination of photos kindly provided by Katerina Achilleos (University of Otago, New Zealand), we can also exclude the conspecificity of M. hastingsae and the colony that Achilleos et al (2020) reported as Microporella aff. coronata from a shipwreck off Cyprus.…”
Section: Discussionmentioning
confidence: 95%
“…The species has so far been identified only from ca one hundred-year-old material originating from the Red Sea and the Red Sea-facing portions of the Suez Canal. It has not been detected in the Levantine Sea, despite the extensive sampling performed at the beginning of this century along the coasts of Cyprus (Achilleos et al, 2020(Achilleos et al, , on surveys of the 2011(Achilleos et al, -2018 and Lebanon (Harmelin, 2014;Harmelin et al, 2016Harmelin et al, , on surveys performed between 1992Harmelin et al, and 2003 for one in 1968, oddly without Microporella species listed in the former one). We can confidently rule out the overlooking of M. hastingsae by Harmelin et al (2016) because he coauthored the description of the species (Harmelin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been commonly found in several localities and habitats by one of us (AR) including: coralligenous concretions at 35-55 m depth in the Gulf of Noto, SE Ionian coast of Sicily [39] and pillar-like coralligenous structures at 30 m depth in the same area [26,40]; circalittoral detritic bottoms in the Gulf of Noto (33-78 m living and 33-83 dead) [26], detritic bottoms of the outer shelf in the Ciclopi Island Marine Protected Area (AR, personal observations), and off Ustica Island (60 m living and dead) [41,42]; several submarine caves from the Ionian coast of Sicily [23,28,43]. Additional plausible records are from: Marseille area [9] and other localities along the Mediterranean French coast in: coralligenous habitats, dark and semidark caves, and clastic biogenic bottoms [11,35,44,45]; including the underside of small substrata [45,46] underwater tunnels in Medes Island, Catalan coast [47]; off the coast of Latium, Volcano Isle (S Tyrrhenian Sea), Tunisia [16]; the Aegean Sea in the Karpathos Strait (29-80 m), Kythira Island (66 m) and Santorini (100-128 m) [14]; localities along the southern coast of Chios Island, i.e., Cape Masticho (15-60 m), Venetiko (12-50 m), and Emborios Bay (1-15 m) but reported as O. angulosa [15], and off Milos Island [48]; Cyprus [8,49], and the coasts of Turkey [50] and Lebanon [18]. Autozooids irregularly or quincuncially arranged, large (mean ± SD: 427 ± 28 × 326 ± 34 μm) and thick, slightly longer than wide (mean L/W: 1.31); generally ovoidal but often rounded polygonal and arched distally; zooidal boundaries raised and outlined by narrow grooves (Figures 4A and 5A,B-D, 6A,B,E).…”
Section: Distributionmentioning
confidence: 99%
“…The Mediterranean Sea hosts a high proportion of the global biodiversity with approximately 17,000 species [2], including 556 bryozoans which account for about 10% of the world known diversity for the phylum [3]. However, large sectors (mostly in the eastern and southern Mediterranean) and several habitats (e.g., remote and hardly accessible dark habitats) remain understudied, as recently demonstrated [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%